RADIOCARBON DATING OF MID-HOLOCENE MEGAFLOOD DEPOSITS IN THE JOKULSA A FJOLLUM, NORTH ICELAND - Kirkbride M.P.; Dugmore A.J.; Brazier V. (My University, 2006)
Two megafloods in the canyon of the Jokulsi i FjOllum, the major northern routeway for glaciovolcanic floods from VatnajOkull, have been closely dated by 14C AMS dates from Betula macrofossils within peat immediately below beds of flood-deposited sand. Ages of c. 4415 and c. 4065 yr BP (5020 and 4610 cal. yr BP) are consistent with the presence of the Hekla 4 tephra (c. 3830 yr BP) resting on the upper surface of the younger flood sand. These sediments are correlated across the JOkulsa a Fjollum canyon with the upper flood sands in a stack recording around 16 flood events. Deposits on both sides of the canyon were trimmed by the last megaflood after the Hekla 3 tephra fall at c. 2900 yr BP, and the highest Holocene flood stages were at the culmination of a series peaking at c. 3500 yr BP. These floods have wider palaeoclimatic significance because they require the formation of large subglacial reservoirs below VatnajOkull. Therefore, the dated floods indicate that a large composite ice cap covered volcanoes in the southeastern highlands through the early and middle Holocene, and that flood routeways largely switched to the south after c. 3500 yr BP.
Keywords: JOKULHLAUPS; RADIOCARBON DATING; SLACKWATER SEDIMENT; MEGAFLOODS; MID-HOLOCENE; ICELAND; Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен